The impact of different ovarian stimulation protocols on embryological stage and efectiveness of ivf cycles - M G Andreeva; A G Syrkasheva; N V Dolgushina; E A Kalinina (IP Berlin A.V., 2016)
There are controversial data about the effect of different controlled ovarian hyperstimulation (COS) protocols on embryological stage and in vitro fertilization (ivf) outcomes. The aim of our study was to evaluate embryological and clinical outcomes according to COS protocol.Material and methods. This prospective cohort study included 521 patients treated with ivf. The patients were divided into the following 5 groups: group 1 - women treated with gonadotrophin-releasing hormone (GnRH) antagonists: subgroup 1a (n=143) - triggering of final oocyte maturation with human chorionic gonadotropin, subgroup 1b (n=85) - with GnRH agonist. Group 2 (n=119) - women treated with GnRH agonists, group 3 (n=82) - women treated in «modified» natural cycle, group 4 (n=92) - women treated with GnRH antagonists and corifollitropin alfa.Results. The lowest percent of empty follicles (78.9%) was observed in group 2. The proportion of mature oocytes (number of mature oocytes|number of cumulus-oocyte complexes) was highest in groups 1a and 2 in comparison with groups 1b and 4 (87.9 and 87.2% vs. 84.0 and 81.9%, respectively). The fertilization rate was maximal in group of women with «modified» natural cycle. The proportion of embryos with different morphological quality was similar in the groups. A clinical pregnancy was observed in 48 (33.6%) cases in group 1a, in 26 (30.6%) patients in group 1b, in 39 (32.8%) casesin group 2 in 7 (8.5%) cases in group 3 and in 17 (18.5%) cases in group 4 (p